2019
DOI: 10.1094/mpmi-10-18-0275-r
|View full text |Cite
|
Sign up to set email alerts
|

An Effector, BxSapB1, Induces Cell Death and Contributes to Virulence in the Pine Wood Nematode Bursaphelenchus xylophilus

Abstract: The pine wood nematode (PWN) Bursaphelenchus xylophilus has caused serious damage to pine forests in China. Effectors secreted by phytonematodes play a role in host infection. We identified and characterized an effector, BxSapB1, based on the B. xylophilus transcriptome at the early stages of infection and the transient expression of proteins in Nicotiana benthamiana. BxSapB1 triggered cell death in N. benthamiana when secreted into the apoplast, and this effect was independent of N. benthamiana brassinosteroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 79 publications
0
49
0
Order By: Relevance
“…In our previous study, another saposin‐like protein, BxSapB1 was identified and characterized and was also proven to induce cell death in N. benthamiana (Hu et al., 2019). A comparison between the two proteins was conducted in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study, another saposin‐like protein, BxSapB1 was identified and characterized and was also proven to induce cell death in N. benthamiana (Hu et al., 2019). A comparison between the two proteins was conducted in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to differences in sequence lengths, the placement of the SapB domain and promoter motifs, there were two further major differences. First, BxSapB2 was upregulated in the transcriptome of B. xylophilus (2.5 hr post‐infection) but was not upregulated in the transcriptome of B. xylophilus (6, 12 and 24 hr post‐inoculation) (Hu et al., 2019; Tsai et al., 2016). BxSapB1 was upregulated in the two above transcriptomes of B. xylophilus .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, water in which invasive stage juvenile nematodes have been incubated (NemaWater) has been shown to elicit PTI responses in host plants (Mendy et al , 2017, Wang'ombe, 2019). However, PAMPs have yet to be described from B. xylphilus , although several effectors have been characterized, including glycoside hydrolase family 45 (GH45) cellulases, pectate lyases, expansins, β‐1,3‐endoglucanases, and the novel effector BxSapB1 (Hu et al , 2019).…”
Section: Introductionmentioning
confidence: 99%